PENGETAHUAN DENGAN TINDAKAN PENCEGAHAN PENULARAN TUBERKULOSIS PARU DI UPT PUSKESMAS HELVETIA MEDAN: PENGETAHUAN DENGAN TINDAKAN PENCEGAHAN PENULARAN TUBERKULOSIS PARU - Leny Suarni; Irma Handayani; Ilham Syahputra Siregar (Jurnal Penelitian Keperawatan Medik, 2026)
Tuberculosis (TB) remains a major public health problem worldwide, with the incidence continuing to increase each year. One of the contributing factors to the high number of TB cases is the limited knowledge and inadequate preventive practices among family members of patients with pulmonary tuberculosis. This study aimed to analyze the relationship between the level of knowledge and preventive behaviors regarding pulmonary TB transmission among families of TB patients at the Helvetia Public Health Center, Medan. This study employed a quantitative method using a correlational design with a cross-sectional approach. A total of 48 respondents, consisting of family members of TB patients, were selected through purposive sampling. The findings revealed that most respondents had a moderate level of knowledge (54.2%), followed by low knowledge (31.3%) and good knowledge (14.6%). In terms of preventive behaviors, 41.7% of respondents demonstrated moderately good prevention practices, 35.4% showed good practices, and 22.9% had poor preventive behaviors. Statistical analysis using the Chi-Square test showed a p-value of 0.004 (p < 0.05), indicating a significant relationship between the level of knowledge and pulmonary TB transmission prevention behaviors among family members of TB patients. These findings suggest that improving family knowledge may contribute to better prevention practices in reducing TB transmission. Therefore, healthcare workers and community health volunteers are encouraged to strengthen educational interventions related to TB prevention and promote early detection when symptoms of pulmonary TB are identified.